New procedure for the simulation of belowground competition can improve the performance of forest simulation models - Shanin, Vladimir; Mäkipää, Raisa; Shashkov, Maxim; Ivanova, Natalya; Shestibratov, Konstantin; Moskalenko, Svetlana; Rocheva, Liliya; Grabarnik, Pavel; Bobkova, Kapitolina; Manov, Alexey; Osipov, Andrey; Burnasheva, Elvira; et al. (Springer, 2015)
The major part of existing models of belowground competition in mixed forest stands is limited in explaining the spatial distribution of roots as a response to competitive pressure from neighbours and heterogeneity of soil properties. We are presenting a new spatially explicit and multi-layered discrete model of belowground competition, RootInt (ROOTs INTake). It describes spatial distribution of belowground biomass and allows simulation of competition between trees for soil nutrients. The tree-specific area of root zone is calculated on the basis of stem diameter, with site-specific modifiers to account for the effect of soil fertility and moisture. The shape of root zone is dependent on the amount of available nitrogen in the current cell, distance between this cell and the stem base, and the mass of roots of other plants. RootInt was incorporated into ecosystem model EFIMOD to refine the existing description of belowground competition in forest stands with multiple cohorts and tree species. The results of simulation showed that bringing more complexity into structure of stand (including initial spatial locations of trees, species composition and age structure, vertical structure of canopy) resulted in higher spatial variation in competition intensity, as well as in higher rates of resource uptake. This indicates that stands with complex canopy structure had high plasticity in their root systems and were adapted to intensive competition for soil resources.
Keywords: process-based model; root systems; forest ecosystems; adaptation; meta-analysis